Emotions of Orthopaedic Arthroplasty Patients: A European Survey - Zabalegui-Yárnoz, Adelaida; Cabrera, Esther; Cano, Sara; Copanitsanou, Panagiota P.; Fatkulina, Natalja; Katajisto, Jouko K.; Papastavrou, Evridiki; Sigurdardottir, Arun K.; Valkeapää, Kirsi; Leino-Kilpi, Helena T. (My University, 2020)
METHODS: This was a pre/post-observational study examining patients' emotions before and during elective knee or hip replacement surgery for osteoarthritis in seven European Union countries to identify factors related to better emotional status at discharge. INSTRUMENTS: In addition to demographic data, information was collected on quality of life (EuroQoL five-dimension questionnaire), hospital expectations (Knowledge Expectations of Hospital Patients Scale), symptoms, and experienced emotions. ANALYSIS: Total negative emotions scores at baseline and discharge were transformed into median values. Multivariate analysis identified the baseline factors related to better emotional status at discharge. RESULTS: Patients (n = 1,590), mean age 66.7 years (SD = 10.6), had a significant reduction in the frequency of total negative emotions at discharge as compared with baseline. The multivariate model showed better health status (odds ratio [OR] = 1.012; p = .004), better emotional status at baseline (≥24 points), and shorter duration of hospital stay (OR = 0.960; p = .011) as independent factors associated with better emotional status at discharge (OR = 4.297; p = .001). CONCLUSIONS: Patients undergoing elective knee or hip replacement surgery for osteoarthritis improve their emotional status during hospitalization, with fewer negative emotions at discharge. Good emotional status, feeling of higher health status at baseline, and shorter hospitalization were independently associated with better emotional status at discharge.
Keywords: Arthroplasty; Hip Replacement; Depression; Elective Surgical Procedures; Emotions; Patient Discharge